2017
DOI: 10.1002/cam4.1218
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of telomerase activity and induction of apoptosis by Rhodospirillum rubrum L‐asparaginase in cancer Jurkat cell line and normal human CD4+ T lymphocytes

Abstract: Rhodospirillum rubrum L‐asparaginase mutant E149R, V150P, F151T (RrA) down‐regulates telomerase activity due to its ability to inhibit the expression of telomerase catalytic subunit hTERT. The aim of this study was to define the effect of short‐term and long‐term RrA exposure on proliferation of cancer Jurkat cell line and normal human CD4+ T lymphocytes. RrA could inhibit telomerase activity in dose‐ and time‐dependent manner in both Jurkat and normal CD4+ T cells. Continuous RrA exposure of these cells resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
0
22
0
2
Order By: Relevance
“…It was previously shown that RrA can inhibit telomerase in cancer cells and normal human lymphocytes by inhibiting the expression of its catalytic subunit hTERT (human telomerase reverse transcriptase) [ 10 , 11 ]. We checked whether other L-ASNases have similar effects on telomerase by incubating Jurkat cells with enzymes of different origins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously shown that RrA can inhibit telomerase in cancer cells and normal human lymphocytes by inhibiting the expression of its catalytic subunit hTERT (human telomerase reverse transcriptase) [ 10 , 11 ]. We checked whether other L-ASNases have similar effects on telomerase by incubating Jurkat cells with enzymes of different origins.…”
Section: Resultsmentioning
confidence: 99%
“…An unexpected antitelomerase activity came from the observation that the rather well-studied L-ASNase from Rhodospirillum rubrum (RrA) can suppress proliferation and induces replicative senescence in acute leukemia Jurkat cancer cell line at non-toxic concentrations [ 11 ]. All known mechanisms of antiproliferative activity of L-ASNases rely on their ability to hydrolyze L-asparagine in the cell microenvironment or in a close proximity to cellular membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…activity in vivo [14][15][16][17][18]. RrA subunit has small molecular weight (18 kDa; monomer contains 172 amino acids).…”
Section: S3mentioning
confidence: 99%
“…KVS NIMA LB through), spreading 100 µm of protein solution with Hamilton syringe and compressing protein monolayer to a surface pressure of 20 mN/m by means of a Langmuir-Blodgett teflon barriers [16][17][18]…”
Section: Lb Nanotemplate Techniquementioning
confidence: 99%